Analisis Financial Distress pada Perusahaan Sektor Perdagangan, Jasa dan Investasi yang Terdaftar di Bursa Efek Indonesia - Nurwahida, Rachma Putri; Margasari, Naning (BUDGETING : Journal of Business, Management and Accounting, 2024)
Identification of financial distress conditions was an important thing for companies to anticipate bankruptcy. This study was aimed to analyze the financial distress model in trading, service and investment sector companies in 2018-2020 using the Altman Z-Score, Grover, Springate and Zmijewski modified models. In addition, this was also aimed to determine the level of accuracy of the Modified Altman Z-Score, Grover, Springate and Zmijewski models. This research was included in the type of quantitative research. The research population consisted of all trading, service and investment companies listed on the Indonesian Stock Exchange during the period 2018-2020. This study used purposive sampling technique with total 133 companies. The data analysis model used in this study were the Altman Z-Score, Grover, Springate and Zmijewski Modified Model. It was conducted by taking secondary data from the Indonesian Stock Exchange website (www.idx.co.id). Based on the results of the analysis that had been carried out, the results showed that: (1) There were 55,89% companies experiencing financial distress and 44,11% non-financial distress using the Springate model on the analysis; (2) On the analysis using the Altman Z-Score Modified model, there were 25.81% companies experiencing financial distress and 59,65% nonfinancial distress; (3) Using the Zmijewski model, it showed that 20,80% of companies experienced financial distress and 79,20% of non-financial distress; (4) Using the Grover model, it showed that 20.80% of companies experienced financial distress and 77,94% of non-financial distress; (5) The Springate model was the most accurate model in analyzing the financial distress. Keywords: Accuracy Level, Altman Z-Score Modification, Financial Distress, Grover, Springate, Zmijewski.